Violência psicológica nos relacionamentos amorosos: um estudo sob a ótica daTeoria das Representações sociais - Neves, Beatriz Motta (2022)
The existence of abusive romantic relationships denounces the predominance of a hierarchical and unequal relationship between genders, which can legitimize the occurrence of violence and discrimination, as well as the position of subordination insistently assigned to women. Violence against women is thus included within the category of gender violence, which is perpetuated in various ways within society. However, subtle actions, such as blackmail, humiliation, insulting, and manipulation, which characterize a form of violence, are not always understood as abusive, being constantly naturalized. This paper, from the perspective of the Theory of Social Representations, proposed to investigate understandings about gender and violence against women, focusing on psychological violence, as well as coping strategies used by women in cases of abusive and/or violent relationships. Study 1 had the general objective of investigating social representations of violence against women, with a focus on psychological violence, and social representations of gender contained in newspaper articles that discussed abusive relationships, as well as verifying if such news articles made references to strategies for combating violence against women. It consisted of documentary research, which was carried out using as data source 222 articles from Istoé Magazine, from the period between 2012 and 2021, selected through the search terms "violence against women", "psychological violence" and "gender violence". Study 2 involved semi-structured interviews with 16 participants aiming to investigate social representations of violence against women, with a focus on psychological violence, of women who have experienced and/or are experiencing an abusive relationship, as well as coping strategies reported by them. In addition to the questions presented verbally, the interview script included, at first, two questions that used images to introduce the theme of interest and let the participants speak freely about what they thought about the contents of the images. The material from the documental research and the interviews were submitted to the IRAMUTEQ software processing (Interface de R pour les Analyses Multidimensionnelles de Textes et de Questionnaires) and, in a complementary way, the thematic content analysis technique was also used in both studies (exclusively in the set of articles selected based on the descriptor psychological violence; and in the questions of the semi-structured interview script that used visual resources). As results of study 1, we highlight the reports that addressed violence against women focused mainly on criminal and statistical aspects, and cases involving people known in the media; the reports did not bring an explicit conceptualization about gender, but some indicated cultural and social aspects related to the occurrence of violence against women; the coping strategies were described predominantly associated with legal/punitive actions. Regarding the findings of study 2, we identified contents of social representations of gender and violence against women sustained on sociocultural aspects, which indicate hierarchical power relations between men and women. The women interviewed mentioned using different strategies when faced with the context of violence, some of them being more individual (searching for information and approaching feminist agendas through reading, for example), while others involved in seeking help through social and/or professional support. In regards to the meanings of psychological violence, it was verified that both the articles (study 1) and the interviews (study 2) did not bring a conceptual definition of it, focusing more on practices that characterized this type of violence (disqualification, threats, manipulation, yelling, humiliation, insulting, among others). It is noteworthy that the phenomenon of psychological violence is difficult to approach and that, for this reason, it was necessary to follow an indirect path to try to access it. However, it is considered an advance, to some extent, that this typology was mentioned in the magazine articles analyzed, and that the participants demonstrated they could identify it within the experiences narrated. It is hoped that the present investigation, which tried to bring some more clues about the phenomenon of psychological violence in romantic relationships, will serve as a kick-start for new theoretical and methodological approaches on the subject, helping to fill the remaining gaps.